2014
DOI: 10.5455/ijmsph.2014.020820142
|View full text |Cite
|
Sign up to set email alerts
|

Newborn care practices of mothers in rural areas of Navsari district

Abstract: Background: Newborn mortality is one of the world's most neglected health problems. It is estimated that globally four million newborns die before they reach 1 month of age and another four million are stillborn every year. Aims & Objectives:(1) To study the maternal care in terms of Antenatal, Intranatal and Postnatal care practices; (2) To assess newborn care practices in rural areas. Materials and Methods:A cross-sectional study in rural areas of Navsari district, Gujarat, included 243 women who had one chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…6,[13][14][15] It was observed in present study that 91% of the mothers received iron and folic acid supplementation, this results are quite comparable to the observation of NFHS-4, the percentage of women who either received or bought IFA tablets was 77.7%, Gupta et al study reported that 93.7% mothers received IFA tablets and Gandhi et al study also revealed that all the mothers had received Iron supplements during ANC visit. 6,[16][17][18] In the present study 95% of mothers immunized with adequate dose of Tetanus Toxoid, this findings is relatively compared to the result of Annual Health Survey (AHS) 2012-13 Uttar Pradesh and Lucknow district which is 83.2% and 87.5% respectively and also supported by some others Indian authors in their study. 6,19,20 In the present study, 75.5% mothers were delivered in health facility in which 52% at Government health facility and 24% in private health facility while 24.5% mothers were delivered at home.…”
Section: Discussionsupporting
confidence: 83%
“…6,[13][14][15] It was observed in present study that 91% of the mothers received iron and folic acid supplementation, this results are quite comparable to the observation of NFHS-4, the percentage of women who either received or bought IFA tablets was 77.7%, Gupta et al study reported that 93.7% mothers received IFA tablets and Gandhi et al study also revealed that all the mothers had received Iron supplements during ANC visit. 6,[16][17][18] In the present study 95% of mothers immunized with adequate dose of Tetanus Toxoid, this findings is relatively compared to the result of Annual Health Survey (AHS) 2012-13 Uttar Pradesh and Lucknow district which is 83.2% and 87.5% respectively and also supported by some others Indian authors in their study. 6,19,20 In the present study, 75.5% mothers were delivered in health facility in which 52% at Government health facility and 24% in private health facility while 24.5% mothers were delivered at home.…”
Section: Discussionsupporting
confidence: 83%
“…31.5% of mothers believe that prelacteal feeds can be offered to newborn. This prevalence of prelacteal feeds in the present study is comparable to Ausvi Samina et al [7] (32.9%) and Shreyash J Gandhi et al [8] (32.1%). Higher rates are reported by P. Gupta et al [9] (50.6%) and Devang Raval et al [10] (61.9%).…”
Section: Discussionsupporting
confidence: 80%
“…[15] This can make the newborn vulnerable to hypothermia. The practice of bathing newborn immediately after birth in present study is 36.7% and 37.8% in Shreyash J Gandhi et al [8] Sartaj Ahmad et al [16] reported very high prevalence (76.6%) of this harmful practice.…”
Section: Discussionmentioning
confidence: 91%
“…6 Gandhi et al in their study showed that all the mothers under study had adequate ANC check-ups. 9 In the present study more deliveries were caesarean 115 (60.5), normal vaginal delivery were lesser 74 (38.9%) owing to the fact that QMH is a tertiary care facility where many referral cases from secondary and primary care centers are managed. Similar results were seen in the study by Madhu et al in that total of 90% of the deliveries were hospital deliveries and 10% were home deliveries.…”
Section: Discussionmentioning
confidence: 46%